Influence of Concentration on Surface Tension & Viscosity of Tamarind (Tamarindus Indica) Seed Gum - Sunita Thakur; Pramod Kumar Sharma; Rishabha Malviya (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2017)
The influence of concentration (0.125-1%w/v) on viscosity and surface tension of tamarind gum has been studied. This research establishes a direct relationship between concentration and viscosity. The intrinsic viscosity was found out to be 0.696dl/g. The value of the Huggins constant was about 0.32 indicates the presence of molecular association. Huggins parameter 'b' (5.042) indicates that tamarind gum has random coil confirmation. A Kraemer constant of 0.180 gives information about the molecular association between gum molecules. Power law model has been used for predicting the molecular confirmation. A coil overlaps parameter of 0.4484 is the indication of presence of molecular entanglement. Their Values indicates polymer chain structure which are coiled & interpenetrating & overlapping with one another. The present investigation shows that surface tension decreases with an increase in the concentration of gum in solution. From these findings, it can be concluded that the gum molecules have a large interaction with more liquid than present in the air.